(untitled) (Al-Qamar, 2020)
In the saga of feminist history, the dawn of third decade of the present millennium is at such a juncture that it is questioning a surrogate representation of feminism. Some critics problematize the phenomenon of feminist representation and are of the opinion that truth is being displaced by certainty as displayed in ideas, pictures, and representations. Studying the progression of such representations and portrayal of feminism resulting mostly in a noise and obscenity traversing the phenomenon of an unwomanly woman this paper foregrounds the importance of actual women’s rights. Making use some oracular ideas of Suleri suggesting the need for alternative answers, this paper argues that sloganeering of iconoclastic and idiosyncratic typecasting of feminism need not be imposed on such a colossal scale across academic, polemic, and cultural platforms. Presenting this pervasive issue of feminism, womanism, and women’s rights in the light of alternate modes of understanding, this paper investigates the importance and relevance of revisiting the injunctions of our religious text and Iqbal’s feminist philosophy.